G. L. S. Shackle. The years of high theory : invention and tradition in economic thought, 1926-1939. Londres : Cambridge University Press, 1967. 387 p. - García Rocha, Adalberto (Estudios Demográficos y Urbanos, 1973)
G. L. S. SHACKLE, The Years of High Theory. Invention and Tradition in Economic Thought, 1926-1939, Londres, Cambridge University Press, 1967.